From Rural Underdevelopment to Innovation: The Strategic Role of Skilled Labor in the South-East Development Region of Romania - Daniela Lavinia Balasan; Dragoș Horia Buhociu (Journal of Agriculture and Rural Development Studies, 2025)
Romania’s South-East Development Region, composed of the counties of Brăila, Buzău, Constanța, Galați, Tulcea, and Vrancea, faces systemic challenges in developing human resources in rural areas, particularly in relation to skilled labor. Inter-county disparities are evident: while counties like Constanța and Galați benefit from more advanced educational infrastructure and stronger connections to the labor market, counties such as Tulcea and Vrancea lag significantly behind in terms of vocational training and youth integration. Compared to the Centre Region, which has implemented more coherent models of dual education and public-private partnerships, the South-East Region remains a largely untapped reservoir of potential. This article analyses the key factors influencing skilled labor in rural areas, highlights the differences among counties within the region, and outlines strategic directions for balanced and sustainable development.